In Vitro Antioxidant Treatment of Semen Samples in Assisted Reproductive Technology: Effects of Myo-Inositol on Nemaspermic Parameters - Mariangela Palmieri; Palma Papale; Antonietta Della Ragione; Giuseppa Quaranta; Giovanni Russo; Sabatino Russo (International Journal of Endocrinology)
Male infertility and the poor quality of sperm seem to be influenced by oxidative stress. In particular, the reactive oxygen species (ROS) mainly produced by morphologically altered spermatozoa affect sperm motility, morphology, and integrity. The aim of this study was to evaluate the efficacy of Myo-Inositol (Myo-Ins) on a number of parameters such as viscosity and total and progressive motility of spermatozoa, in order to better validate its possible practical application in vitro, in order to improve the capacitation protocols commonly used in Assisted Reproductive Technology (ART). A total of 100 fresh and 25 thawed semen samples were analyzed in vitro prior to and after addition of Myo-Ins. Treatment of samples with Myo-Ins showed an increase in the sperm total and progressive motility in both fresh and thawed samples. Furthermore, Myo-Ins proved to be well tolerated by spermatozoa in vitro, demonstrating that it can be efficiently and safely used as antioxidant in the laboratory practice and for preparation of semen samples in ART.